2012
DOI: 10.17221/5994-pse
|View full text |Cite
|
Sign up to set email alerts
|

Road salts effects on soil chemical and microbial properties at grassland and forest site in protected natural areas

Abstract: Road salting is used as a dominant way to keep road safety in winter, even in the protected natural areas. In our study, possible effects of winter road salting on soil microorganisms in close road vicinity were investigated. Soil chemical and microbial properties were monitored at a forest site in the Krkonoše Mountains national park and at a grassland site in the Kokořínsko protected landscape area (both located in the Czech Republic) in two sampling campaigns (autumn and spring). Effects of road salting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…On the other hand, concentration of TOC increases gradually in distance of more than 200 m of the valley side of the road.It can suggest that TOC increases in the samples taken from relatively flat areas where sediments were deposited. This observation is accordance with the previous research, which reported that concentration of TOC in soil apparently increases with increasing distance from the road (25). app reported that concentration of TOC in soil accordance with the previous research, which reported that concentration of TOC in soil…”
Section: Effect Of Distance From the Road On Tocsupporting
confidence: 93%
“…On the other hand, concentration of TOC increases gradually in distance of more than 200 m of the valley side of the road.It can suggest that TOC increases in the samples taken from relatively flat areas where sediments were deposited. This observation is accordance with the previous research, which reported that concentration of TOC in soil apparently increases with increasing distance from the road (25). app reported that concentration of TOC in soil accordance with the previous research, which reported that concentration of TOC in soil…”
Section: Effect Of Distance From the Road On Tocsupporting
confidence: 93%
“…The studies have shown that 20-63% of road salt is transported through the air and is deposited at a distance of 2-40 m from the road (Blomqvist & Johansson 1999), more than 90% of salt is deposited at the distance of 15-20 m from the road edge (Hofman et al 2012), chloride concentrations decline on average ten times at a distance of 10 m from the road edge (Findlay & Kelly 2011) and the maximum distance over which salt is transported is proportional to the speed of vehicles on the roads (McBean & Al-Nassri 1987). The presented interdependencies are clearly visible for samples collected from the Planty Gardens at a distance of approx.…”
Section: Resultsmentioning
confidence: 99%
“…Younger plants are considered to be less tolerant of salinity due to their shallower roots. Elevated salinity also has a negative impact on microorganisms, additionally disturbing the soil environment (Czerniawska-Kusza et al 2004, Yuan et al 2007, Černohlávková et al 2008, Hofman et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the diversity of 13 C‐ labelled bacteria differed highly from those of the roadside soils: in soil D and F, ferrocyanide was used as C source mainly by Actinomycetales , while in soil W members of Acidobacteria (Gp3, Gp4, Gp6), Gemmatimonadetes ( Gemmatimonas ) and Gammaproteobacteria ( Thermomonas , unclassified Xanthomonadaceae ) assimilated the 13 C. All those taxa were previously found to be enriched in bioreactors containing mining effluent, indicating their capacity to degrade thiocyanate and cyanide (Kantor et al ., ). Surprisingly, neither Kineosporia nor Mycobacterium assimilated ferrocyanide‐derived C in soil W although their presence at similar abundances when compared with soil D and F. This indicates an adaptation of the microbial community on long‐term ferrocyanide application and consequently its permanent presence as additional C source: in soils first exposed to ferrocyanide, various microorganisms assimilate the new available C but at the end were outcompeted by Actinomycetales , resulting in their increased abundance in roadside soils when compared with soil W. However, it has to be taken into account that ferrocyanide is not applied purely to the road environment but as anticaking agent via deicing salts that itself could impact microbial soil community (Cernohlavkova et al ., ; Hofman et al ., ). Although we cannot exclude a long‐term salt related influence, we assume that the impact of previous applied deicers could be neglected in our system as (i) the soil was sampled in November before road deicing salt was first applied in the actual winter period and (ii) salt applied during the last winter was quickly leached due to high precipitation (1280 mm y −1 ) in the sampling area.…”
Section: Discussionmentioning
confidence: 99%